Pembuatan Dan Pengujian Alat Ukur Intensitas Cahaya Lepas Pantai Menggunakan Sensor BH-1750 - Alfarez, Abel (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2024)
Utilization of solar energy sources is an alternative energy to save fossil energy. The use of solar panels has been widely implemented both at home, buildings and open fields. The most sources of sunlight are on the beach, because the beach area has an area without exposure to sunlight. Against this background, this study aims to create an instrument for measuring light intensity offshore. The method used is by reviewing literature studies, making light intensity measuring instruments, testing on the beach and analyzing data. The results obtained during the initial test were that the highest light intensity was in minute 10 of 50578 lx with the highest power of 399.5662 W/m2 at 360C. In testing at 09.00-09.30 WIT with a temperature of 460C produced the highest light intensity was in the 15th minute of 56145 lx with the highest power of 443.5455 W/m2. In testing at 10.00-10.30 WIB with a temperature of 490C, the highest light intensity was at 30 minutes of 57853 lx with the highest power of 457.0387 W/m2. And testing at 11.00-11.30 WIB with a temperature of 500C produced the highest light intensity at 75 minutes of 62845 lx with the highest power of 496.4755 W/m2. The conclusion of this study is that a microcontroller-based light intensity measuring instrument can be developed and used in offshore light intensity measurements. Keyword: Light Intensity, Microkontroller, Sensor BH-1750.